Animal Farm by George Orwell "Speech Act" Detection and Alienation Motif Symbol Operator Corpus Analysis Discussion - Majetic, Senka (Eximia, 2023)
The article Animal Farm by George Orwell "Speech Act" Detection and Alienation Motif Symbol Operator Corpus Analysis Discussion is a practical presentation of the parallel interaction between Language and Society! Speech/Social Acts (according to Searle) Classification Operator and Alienation Motif Symbol Corpus Analysis Operator have been exploited. The test sample, chapter 1 of the novel Animal Farm (pages 4-10) by George Orwell 1944, is being analysed! Null hypothesis: Declarations dominate in the novel Animal Farm by George Orwell 1944 and Null hypothesis Alienation is the background of the novel Animal Farm by George Orwell 1944 are being tested. Marx´s classification of alienation from the product of labour, alienation from the activity of labour, alienation from humanity and society corpus analysis operator have been tested and presented.